SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KELULUSAN HASIL UJIAN AKHIR SEKOLAH MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Suwatri Jura; Sitti Zuhriyah; A. Edeth Fuari (STMIK KHARISMA Makassar, 2017)
Decision support system is an interactive information system which provides information, modeling and manipulation of data. The system is used to support decision-making in the semistructured and unstructured situation where no one knows for sure how the decision should be made. The research describes how to maximize and analyze professionally the determination of students' graduation process after taking the school final exam. This application workflow has four (4) virtues that processes the scoring system, they are the student, teacher, principal, and staff. The research aims (1) to design Decision Support Systems of Final Exam Results using Simple Additive Weighting method (2) to implement the Decision Support Systems of Final Exam Results using Simple Additive Weighting method. The result of research shows that it has been designed and tested the Decision Support Systems of Final Exam using Simple Additive Weighting method at SMPN 1 Pallangga which can produce graduation information and rankings.